Kohtaamisia kentällä Soveltava keskusteluntutkimus ammatillisissa ympäristöissä - Nissi, Riikka; Simonen, Mika; Lehtinen, Esa (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
Societal impact is an integral part of academic research today and researchers are expected to share their findings with research participants. Efforts to develop scientific research and science communication from one-way communication towards different forms of co-creation where the researcher and research participants produce knowledge and negotiate about its meaning and applicability through joint actions are in great demand. For the researcher, such developments have brought a new kind of access into the world of research participants and also novel reflections on one's professional knowledge and identity and their boundaries. This book focuses on the human and social sciences and draws particular attention to the diverse encounters that occur between researchers and research participants at all stages of the research process when studying human subjects and activities. The book presents case studies of applied conversation analysis in a variety of professional contexts. The aim of the book is to shed light on the practices, possibilities, and challenges of applied research within the conversation analytic framework where the research participants' authentic social situations become the target of the researcher's detailed analysis. The articles of the book investigate social interaction in occupational health care, mental health rehabilitation, elderly care, welfare education, theatre rehearsals, social circus, military organization, software development, and workplace community break taking. These articles represent applied conversation analysis in different ways. The results of the research have been used in some of the articles, for example, in developing the professional practices of the workplace community whereas in some other articles the whole study has been undertaken collaboratively between researchers and professionals. Each article is divided into two parts: a conventional research report that analyses the patterns of social interaction in a particular professional setting is followed by a story where the authors reflect on how their study originated, how it progressed, and what kinds of encounters and choices it involved. The stories highlighting reciprocal interactions of the researcher and the research participants across the research process bring forth various voices and perspectives that conventionally are not considered as part of the research report. The book brings important information not only on the interactional phenomena examined in the articles but also on the diverse issues of conducting and applying research in professional contexts. It also discusses the practices and definitions of applied conversation analysis within the broader framework of applied research, universities' third mission, and forms of knowledge and expertise in contemporary society.